2021
DOI: 10.1002/ente.202100478
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dopamine‐Based Boronate Esters with the Organic Base as Highly Efficient, Stable, and Green Catalysts for the Conversion of CO2 with Epoxides to Cyclic Carbonates

Abstract: A series of dopamine‐based mono‐ and dinuclear boronate esters are studied as stable, efficient, and green metal‐free catalysts for coupling CO2 with epoxides under suitable and solvent‐free conditions. Under the optimized reaction conditions, dinuclear boronate esters compared with those with mononuclear compounds display high catalytic activity and selectivity for the chemical conversion of CO2 into cyclic organic carbonates as a valuable product. Ferrocene group containing boronate ester (B4a) display the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 59 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…In addition, some review articles on CO 2 /epoxide coupling reactions by Kleij et al and D'Elia et al have been reported. 27,28 Furthermore, some active organo-catalysts 19,29−31 including boronate esters 32,33 and homogeneous metal complexes fabricated on various ligands like salen 34 and supported surfaces like silica 35,36 and metal centers such as cobalt, 37−47 uninuclear and binuclear aluminum, 48−52 zinc, 53,54 chromium, 55,56 iron, 57,58 tin, 59 silver, 60 scandium and yttrium, 61 and vanadium 62−64 are reported. Among the reported metal complexes, few ruthenium(II) complexes supported by wellknown ligand systems like salen 65 and porphyrin 66 have been studied for the CO 2 /epoxide coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some review articles on CO 2 /epoxide coupling reactions by Kleij et al and D'Elia et al have been reported. 27,28 Furthermore, some active organo-catalysts 19,29−31 including boronate esters 32,33 and homogeneous metal complexes fabricated on various ligands like salen 34 and supported surfaces like silica 35,36 and metal centers such as cobalt, 37−47 uninuclear and binuclear aluminum, 48−52 zinc, 53,54 chromium, 55,56 iron, 57,58 tin, 59 silver, 60 scandium and yttrium, 61 and vanadium 62−64 are reported. Among the reported metal complexes, few ruthenium(II) complexes supported by wellknown ligand systems like salen 65 and porphyrin 66 have been studied for the CO 2 /epoxide coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, various active heterogeneous catalytic systems, including metal oxides, metal carbonates, metal halides, molecular sieves, metal-organic frameworks, and functionalized polymers, , have been described for the CO 2 cycloaddition to epoxides. In addition, some review articles on CO 2 /epoxide coupling reactions by Kleij et al and D’Elia et al have been reported. , Furthermore, some active organo-catalysts , including boronate esters , and homogeneous metal complexes fabricated on various ligands like salen and supported surfaces like silica , and metal centers such as cobalt, uninuclear and binuclear aluminum, zinc, , chromium, , iron, , tin, silver, scandium and yttrium, and vanadium are reported. Among the reported metal complexes, few ruthenium­(II) complexes supported by well-known ligand systems like salen and porphyrin have been studied for the CO 2 /epoxide coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy drives electrochemical CO 2 reduction reaction (CO 2 RR), enabling not only the clean and efficient synthesis of fine chemicals and fuels but also their potential for sustainable production . From the perspective of green chemistry, the chemical conversion of CO 2 and epoxides to cyclic carbonates is considered to be one of the most useful and potential methods to reduce and utilize CO 2 in practical applications. Researchers have synthesized various materials as catalysts to accelerate the conversion of CO 2 and thereby achieve the purpose of carbon reduction, such as ionic liquids, , polymers, , zeolites, heterojunctions, , metal oxides, etc. The development of low-cost and earth-abundant transition-metal materials, such as Co, Ni, and Cu, have been widely investigated in the CO 2 conversion process during the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ke et al 41 described a triethanolamine borate (TEOAB)-TBAB binary system for the preparation of cyclic carbonates at 120 °C and 1.7 MPa of CO 2 pressure (Table 1, entry 5). Kilic et al synthesized a series of N-heterocyclic carbene (NHC)-boronate ester 51 and dopamine-based boronate ester 52 catalysts for the cycloaddition reactions of CO 2 and epoxides, respectively, demonstrating high catalytic activity (Table 1, entries 6 and 7). Darensbourg, Bhat, and co-workers 53 reported a series of bifunctional organoboron-phosphonium catalysts for coupling reactions of CO 2 and epoxides, and achieved high yields of the desired products (Table 1, entry 8).…”
Section: ■ Introductionmentioning
confidence: 99%